2011
DOI: 10.5603/fhc.2011.0018
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of serum levels of matrix metalloproteinase 2 (MMP-2) and its tissue inhibitor (TIMP-2) in gastric cancer

Abstract: Abstract:Matrix metalloproteinase 2 (MMP-2) is able to degrade type IV collagen, and thus plays a key role in the migration of tumor cells. MMP-2 activity is inhibited by its tissue inhibitor (TIMP-2). The imbalance between MMPs and TIMPs may facilitate progression of cancer cells. The aim of this study was to compare the clinical importance of MMP-2 and TIMP-2 to that of classical tumor markers, namely carcinoembryonic antigen (CEA) and carbohydrate antigen in the diagnosis of gastric cancer (GC) by calculat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 27 publications
2
10
0
1
Order By: Relevance
“…Serum concentrations of MMP-2 and TIMP-2 in cancer group were significantly lower than in healthy controls. The obtained results are in accordance with our previous studies on colorectal [25] and gastric cancer [26] and with results of other authors who examined serum or plasma levels of those proteins in malignancies of alimentary tract, e.g. colorectal cancer [27].…”
Section: Discussionsupporting
confidence: 82%
“…Serum concentrations of MMP-2 and TIMP-2 in cancer group were significantly lower than in healthy controls. The obtained results are in accordance with our previous studies on colorectal [25] and gastric cancer [26] and with results of other authors who examined serum or plasma levels of those proteins in malignancies of alimentary tract, e.g. colorectal cancer [27].…”
Section: Discussionsupporting
confidence: 82%
“…31 In general, MMP2 may promote the cleavage of extracellular matrix proteins, leading to the destruction of the basal membrane as well as tumor cell invasion into the connective tissue matrix, thereby resulting in tumor metastasis in GC. 13 In short, the current meta-analysis indicated that MMP2 protein expression may play an important role in the development of GC, suggesting that detection of MMP2 expression may be utilized as an independent prognostic marker for GC.…”
Section: Discussionmentioning
confidence: 94%
“…14 In addition, there is evidence that suggests that an elevated MMP2 level is significantly related to increased tumor metastasis and advanced stomach cancer. 13,15 More importantly, high levels of MMP2 expression in tissue and plasma are strongly correlated with the depth of tumor infiltration, and the severity of lymph node metastasis, distant metastasis, Union International Contre le Cancer (UICC) stage, and poor overall survival (OS). This could be an indication that MMP2 expression could be of value as a prognostic marker for GC patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, elevated levels of MMP-2 and TIMP-2 have been correlated to distant metastasis in serum samples. [105] The incidence of high levels of MMP14 in bone marrow and peripheral blood detected by qPCR has been correlated with peritoneal dissemination. [101] The expression of MMP7 (mRNA/protein) in tumor specimens detected by RT-PCR and immunohistochemistry has also been associated with this parameter.…”
Section: Matrix Metalloproteinases and Their Tissue Inhibitors In Gasmentioning
confidence: 99%